Keterikatan Kerja pada Generasi Z Ditinjau dari Kebahagiaan Karyawan dan Kinerja Adaptif - Dian Juliarti Bantam; Tatang Sulaiman; Muhammad Erwan Syah; Fonny Dameaty Hutagalung (Indonesian Psychological Research, 2025)
Work engagement is one component that can predict reduced turnover in Indonesia. Generation Z employees with high work engagement feel happier and can adjust their performance in uncertain situations. This study explores the role of employee happiness and adaptive performance on work engagement in Generation Z employees in Indonesia. This quantitative correlational study involved 342 participants of Generation Z employees who has worked for at least 1 year. The sampling technique in this study was purposive sampling.  This study uses three measurement for data collection, namely the employee happiness, adaptive performance, and work engagement scales which were administered using the Google form platform. Data were analyzed using multiple linear regression analysis techniques conducted on SPSS. The results showed that employee happiness and adaptive performance were significantly associated with work engagement among Generation Z employees and explain 45.4% of the variance. This study highlights the needs of future studies to further explore other variable that may affect work engagement beyond to the two variables that have been studied. In addition, the result provides a theoretical basis in developing employee engagement programs for Generation Z employees.